The Influence of Guided Inquiry Models on Science Process Skills - Puspito, Dhimas Rinda Adi; Supardi, Kasmadi Imam; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2021)
Preliminary observations of researchers related to science process skills in grade IV elementary school showed low results. This is due to the learning methods carried out by the teacher still applying conventional learning so that students are passive in learning. The purpose f this research was; (1) to determine the effect of guided inquiry learning models on students 'science process skills and (2) determine the magnitude of the influence of guided inquiry learning models on students' science process skills. This research uses a quantitative research approach that is a quasi-experimental method with a research design used pretest-posttest control group design. This design involves two groups of subjects; guided inquiry model was employed in experimental class and the other class received conventional learning model. The results of this study indicate that the guided inquiry model influences students' science process skills and there are differences in students' science process skills between the experimental class and the control class. In conclusion, the guided inquiry model succeeded in improving the science process skills of students.